DEKADENSI MORAL GENERASI MUDA DALAM AL-QUR'AN (STUDI TAFSIR MAUDHU'I) - Abdul Majid, Jeffry; Mashuri, M. Mukhid; Zainuddin, Ahmad; Mahmud, Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the phenomenon of moral decadence among the younger generation from the perspective of the Qur’an using a thematic tafsir (maudhu’i) approach. The research is motivated by the increasing moral decline among young people, reflected in behaviors such as weakened respect for others, growing individualism, misuse of technology, free association, and decreasing adherence to religious and social values. This study aims to analyze moral decadence from religious, social, and Qur’anic perspectives and to identify Qur’anic solutions for strengthening the moral character of the younger generation. The method employed is thematic tafsir through the collection, examination, and analysis of Qur’anic verses related to morality, supported by the interpretation of Wahbah al-Zuhayli in Tafsir al-Munir. The findings reveal that the Qur’an provides comprehensive moral principles, including justice, honesty, self-control, respect for parents, guarding speech, avoiding immoral behavior, and following the example of Prophet Muhammad. Moral decadence is influenced by internal factors, such as weak faith and identity crises, as well as external factors, including family environment, social influences, media exposure, and globalization. The study concludes that Qur’anic moral values remain highly relevant as preventive and curative solutions to address the moral crisis among the younger generation. Therefore, the implementation of Qur’an-based moral education is essential for fostering individuals and communities with noble character.